2010
DOI: 10.1002/mrm.22434
|View full text |Cite
|
Sign up to set email alerts
|

Max CAPR: High‐resolution 3D contrast‐enhanced MR angiography with acquisition times under 5 seconds

Abstract: High temporal and spatial resolution is desired in imaging of vascular abnormalities having short arterial-to-venous transit times. Methods that exploit temporal correlation to reduce the observed frame time demonstrate temporal blurring, obfuscating bolus dynamics. Previously, a Cartesian acquisition with projection reconstruction-like (CAPR) sampling method has been demonstrated for three-dimensional contrast-enhanced angiographic imaging of the lower legs using two-dimensional sensitivity-encoding accelerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…CAPR MRA followed a previously described technique: 20 mL gadobenate dimeglumine (Multihance, Bracco Imaging, Princeton, New Jersey, USA) injected at 3 ml/sec followed by 20 ml saline at 3 ml/sec (12). Imaging was performed on a 3T scanner (Signa v. 20.0, GE Healthcare, Waukesha, Wisconsin, USA) using a custom eight-element receive array coil designed in-house (13).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CAPR MRA followed a previously described technique: 20 mL gadobenate dimeglumine (Multihance, Bracco Imaging, Princeton, New Jersey, USA) injected at 3 ml/sec followed by 20 ml saline at 3 ml/sec (12). Imaging was performed on a 3T scanner (Signa v. 20.0, GE Healthcare, Waukesha, Wisconsin, USA) using a custom eight-element receive array coil designed in-house (13).…”
Section: Methodsmentioning
confidence: 99%
“…(11-13) The high acceleration provided by 2D SENSE and partial Fourier acceleration, as allowed by the specialized receiver coils, enables imaging the distal runoff vessels with 1 mm isotropic spatial resolution and a frame time of 4.9 sec, and has been shown to provide high fidelity in imaging an advancing contrast bolus. (14) Initial implementation has demonstrated that this technique can be successfully employed to evaluate lower extremity arterial vasculature (12). In this current work we sought to prospectively compare the degree of stenosis assessed by CAPR and CTA, as well as the confidence of the radiologist when evaluating patients with known or suspected peripheral vascular disease with both CAPR and CTA exams performed at our institution.…”
Section: Introductionmentioning
confidence: 99%
“…As portrayed in Fig. , the performance has improved due to many techniques previously identified in this work . Acquisition parameters for a number of these recent reports are listed in Table , and performance noted in Fig.…”
Section: Applicationsmentioning
confidence: 84%
“…Because of the lack of prior image updates, the three initial reconstructed time frames (I5–I7) at the distal station have incomplete sampling of the k Y – k Z plane. However, it has been observed that even without view sharing the image updates can still have good quality (17, 18). Sampling of all four vane sets is done for image I8 and all subsequent frames.…”
Section: Methodsmentioning
confidence: 99%